Student Life at McGill, 1936-1940 - Lévesque, Andrée (Madeleine Parent: Activist, 2005)
Discusses Parent's education at McGill University in the late 1930s, including professors who influenced her and student associations to which she belonged.
Keywords: Biography; Feminism; History; Parent; Madeleine; 1918-2012; Social conditions; Syndicalism; Women political activists